Microbiota Features Associated With a High-Fat/Low-Fiber Diet in Healthy Adults - Bailén, María; Bressa, Carlo; Martínez-López, Sara; González-Soltero, Rocío; Montalvo Lominchar, Maria Gregoria; San Juan, Celia; Larrosa, Mar (Frontiers in Nutrition, 2020)
A high intake of dietary saturated fatty acids (SFAs) is related to an increased risk of obesity, inflammation and cancer-related diseases, and this risk is attenuated only when SFAs are replaced by unsaturated fats and unrefined carbohydrates. The gut microbiota has recently emerged as a new environmental factor in the pathophysiology of these disorders, and is also one of the factors most influenced by diet. We sought to determine whether the gut microbiota of healthy individuals whose intake of SFAs exceeds World Health Organization (WHO) recommendations exhibits features similar to those reported in people with obesity, inflammation, cancer or metabolic disease. Healthy non-obese subjects were divided into two groups based on their SFAs intake. Body composition and gut microbiota composition were analyzed, and associations between bacterial taxa, diet and body fat composition were determined globally and separately by sex. Metagenome functional pathways were predicted by PICRUSt analysis. Subjects whose SFAs intake exceeded WHO recommendations also had a dietary pattern of low fiber intake. This high saturated fat/low fiber diet was associated with a greater sequence abundance of the Anaerotruncus genus, a butyrate producer associated with obesity. Analysis of data of high SFAs intake by sex showed that females presented with a greater abundance of Campylobacter, Blautia, Flavonifractor and Erysipelatoclostridium, whereas males showed higher levels of Anaerotruncus, Eisenbergiella, a genus from the order Clostridiales (FamilyXIIIUCG_001) and two genera from the Lachnospiraceae family. PICRUSt analysis confirmed these data, showing a correlation with a decrease in the abundance of sequences encoding for transporters of some metals such as iron, which is needed to maintain a healthy metabolism. Thus, the microbiota of healthy people on a high SFAs diet contain bacterial taxa (Anaerotruncus, Lachnospiraceae Flavonifractor, Campylobacter, Erysipelotrichacea and Eisenbergiella) that could be related to the development of some diseases, especially obesity and other pro-inflammatory diseases in women. In summary, the present study identifies bacterial taxa that could be considered as early predictors for the onset of different diseases in healthy subjects. Also, sex differences in gut microbiota suggest that women and men differentially benefit from following a specific diet.